MALL BasedWriting Instruction: Assessing the Effectiveness of Digital Platforms Among ESL Learners - Madasamy Lingaraj, Mathivysali; Rajamanickam, Aravind Banumathi; Kumar, Pradeepa; Selvaraj, Lincy Kiruba; Raj Job, John Steward (Digital Technologies Research and Applications, 2025)
Nowadays, mobile‑assisted language learning (MALL) has emerged as a globally adopted approach that builds on the earlier development of computer‑assisted language learning (CALL) by utilizing the accessibility and flexibility of mobile devices to promote independent and self‑directed learning. It enables learners to extend language practice beyond classroom boundaries and provides authentic opportunities to engage with English as a Second Language (ESL). This study investigates the potential of digital platforms, specifically WordPress and Hemingway Editor, in enhancing the writing skills of non‑native English learners within a MALL framework. WordPress offers a collaborative digital space where learners can publish, share, and receive feedback on their writing, while Hemingway Editor provides real‑time analytical feedback to improve readability, grammar, and stylistic accuracy. The research adopted a quantitative design with both control and experimental groups to examine the effectiveness of these platforms. Participants included ESL learners who engaged in structured writing tasks, with their progress assessed through pre‑ and post‑tests. The findings of the study reveal that learners using WordPress and Hemingway Editor demonstrated notable improvements in writing performance when compared to the control group. The integration of these tools not only improved grammatical accuracy and stylistic clarity but also encouraged active participation, reflection, and learner autonomy. The results emphasize the pedagogical value of incorporating MALL strategies into language instruction, particularly for developing essential writing skills among ESL learners. In conclusion, this research affirms that mobile technologies, when strategically integrated into teaching, significantly enhance learning outcomes and offer sustainable pathways for improving ESL writing proficiency.